2015
DOI: 10.1111/epi.12974
|View full text |Cite
|
Sign up to set email alerts
|

Changing profiles of pediatric epilepsy surgery candidates over time: A nationwide single‐center experience from 1990 to 2011

Abstract: SUMMARYObjective: Over the past decades, the number of epilepsy surgeries in children has increased and indications for surgery have broadened. We studied the changes in patient characteristics between 1990 and 2011 in a nationwide cohort and related these to seizure outcome and postoperative medication status. Second, we tried to identify predictors for seizure outcome after pediatric epilepsy surgery. Methods: To study changes over time, we divided this retrospective cohort of 234 children into two consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 38 publications
10
77
0
10
Order By: Relevance
“…Hemb et al . and Lamberink et al . have evaluated a much longer period of epilepsy surgery in their institutions (22 years) compared to ours.…”
Section: Discussionmentioning
confidence: 62%
“…Hemb et al . and Lamberink et al . have evaluated a much longer period of epilepsy surgery in their institutions (22 years) compared to ours.…”
Section: Discussionmentioning
confidence: 62%
“…Multicenter cohorts from other pediatric epilepsy centers even report increasing surgical numbers. Lamberink et al found a threefold increase in surgical interventions per year in a retrospective Dutch cohort of 234 children between 1990 and 2011. Barba et al reported an increase from 56 resective surgeries in 2008 to 182 in 2013‐2014 in a survey from nine Italian epilepsy surgery centers.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be the only difference between pediatric and adult series. Children and adolescents seem to have superior and even improving seizure‐free outcome rates . A meta‐analysis of 36 publications (1993‐2012) comprising 1318 children with temporal and 1259 children with extratemporal resections showed seizure freedom rates (Engel class I) of 76% for temporal lobe resections and 56% for extratemporal resections (minimum follow‐up = 12 months) .…”
Section: Introductionmentioning
confidence: 99%
“…But beyond the importance of a confident localization hypothesis, our data support the recent call for an integrated localization and etiology-centric approach to epilepsy surgery. 24 Thus far the impact of etiology on seizure outcome has been shown in the setting of better seizure outcomes in patients with tumors 25,26 and malformations of cortical development, 27,28 specifically FCD IIb, 29 without strong data to support tailoring of surgical strategy in relation to suspected etiology. In this cohort, we showed that surgical strategy (completeness of lesion resection) affected outcome differentially in suspected FCD lesions as opposed to other malformations of cortical development (PNH, polymicrogyria), hippocampal sclerosis, and encephalomalacia.…”
Section: Discussionmentioning
confidence: 99%